Young Lives, Interrupted: Short-Term Effects of the COVID-19 Pandemic on Adolescents in Low- and Middle-Income Countries. Issue 6 (3rd June 2022) - Favara, Marta; Freund, Richard; Porter, Catherine; Sanchez, Alan; Scott, Douglas
Abstract : We examine the situation of adolescents during the COVID-19 pandemic in four low- and middle-income countries using data from a large-scale phone survey conducted in 2020. The survey was part of Young Lives, a 20-year longitudinal study of two cohorts of young people born in 1994 and 2001 in Ethiopia, India (Andhra Pradesh and Telangana), Peru and Vietnam. We focus on the Younger (19-year-old) Cohort, describing their experiences along multiple dimensions, and assessing how their lives have changed since an earlier survey in 2016. We also compare these young people with an Older Cohort (surveyed at the same age in 2013), using a cross-cohort comparison in the spirit of a difference-in-differences approach. Compared to 2016, and compared with the Older Cohort, the increase in the probability of a loss of household livelihood (income or employment) is both large and significant in all countries. However, a 2020 downturn in self-reported well-being is significant in Ethiopia, India and Peru, but not in Vietnam, the country which experienced particular success in controlling the pandemic during 2020.